MANAGEMEN SUPERVISI DALAM MENINGKATKAN PROFESIONALISME GURU PAI DI MTs GARUNGGUNG KARAWANG JAWA BARAT - Hendi Hidayat; Ahmad Sukandar; Marwan Setiawan (Cross-border, 2021)
The background of the problem is that PAI teachers have not made lesson plans, syllabus, materials. Teaching aids and Student Worksheets (LKS) and evaluation. Supervision management by the principal in the classroom is needed to foster and supervise PAI teachers in improving the professionalism of PAI teachers. The method used is the research method used is a qualitative approach, the types and sources of data use primary data and secondary data, techniques Collecting data using observation. Interviews and documentation studies, data analysis techniques using data triangulation where data is selected that is important and appropriate and then processed to draw conclusions. Syllabus, Basic Competencies (KD), Materials, teaching aids, Student Worksheets (LKS) and student evaluations. After receiving guidance from the principal, the PAI teacher changed what was instructed by the school. second supervisory management. The teacher feels that the principal is finding fault with the PAI teacher, after discussions and approaches between the principal and the teacher have resulted in mutual understanding and improvement professional teachers, and the management of supervision of the three PAI teachers have made a Learning Process Design (RPP). Implementation: The ability of teachers to produce improvements 1) implement (practice) teaching in the classroom. 2) The ability of teachers to manage the classroom. The results or products of PAI teacher professionalism are product criteria (learning outcomes achieved by students) consisting of student learning outcomes from the PAI field of study taught by the teacher, integrating PAI teaching objectives, media or making teaching aids, Teaching Evaluation, Managing the teaching and learning process, guiding student learning better